Evaluation of reference values for phenotypic tests to detect oxacillin resistance in coagulase-negative staphylococci - Pinheiro, Luiza [UNESP]; Mello, Priscila L. [UNESP]; Abraão, Ligia M. [UNESP]; Corrente, José Eduardo [UNESP]; Cunha, Maria De Lourdes R.S. [UNESP] (Taylor & Francis, 2018)
Aim: To evaluate the adequacy of the disc-diffusion test and E-test® compared with detection of mecA for coagulase-negative staphylococci isolated from blood cultures, nasal swabs and wounds. Results: Agreement between all techniques was observed in 65.7% of cases. The greatest discrepancy between mecA/susceptible E-test was observed for non-epidermidis species. A resistance breakpoint ≤19 mm using the oxacillin disc was found to best classify all coagulase-negative staphylococci isolates; Staphylococcus epidermidis, ≤19 mm (oxacillin) and ≤27 mm (cefoxitin); Staphylococcus haemolyticus and Staphylococcus capitis, ≤21 mm (oxacillin) and ≤18 mm (cefoxitin); Staphylococcus warneri, MICs ≥0.75 mg/l. Conclusion: Although no longer recommended by the Clinical Laboratory Standards Institute, we observed some cases in which only the oxacillin disc-diffusion test detected resistance. The discrepancy between phenotypic tests and mecA is probably due to heterogeneity and borderline resistance.
Keywords: coagulase-negative staphylococci; oxacillin resistance; reference breakpoints